A Numerical Model for the Scour Effect on the Bearing Capacity of an Offshore Wind Turbine with a Five-Bucket Jacket Foundation - Hang Zhu; Jijian Lian; Yaohua Guo; Haijun Wang (Journal of Marine Science and Engineering, 2024)
As offshore wind farms move into deeper waters and the capacity of offshore wind turbines (OWTs) increases, a new type of OWT foundation needs to be developed. In this study, a new type of five-bucket jacket foundation (FBJF) was proposed based on the broad application of a multi-bucket jacket foundation (MBJF) in offshore wind farms. The soil around the OWT foundation is subject to scour due to the complex marine environment. To investigate the effects of scouring on the FBJF, a series of local-scour simplified finite-element models of the FBJF were established using ABAQUS, and the effects of scouring depth and the extent on the bearing capacity of the FBJF with the monotonic load were analyzed. Then, the failure envelopes of the FBJF under combined loading were obtained using the fixed-displacement ratio method, and the effects of various scour conditions on the failure envelopes were compared. The results indicate that the failure envelope profile contracts inward, and the bearing capacity decreases with the increasing scouring depth and extent. Furthermore, the failure envelopes of the FBJF under different vertical loads were calculated, and the FV-FH-FM failure envelopes of the FBJF were obtained through interpolation. Finally, the effects of different scour conditions on the FV-FH-FM failure envelopes of the FBJF were analyzed. The results show that the FV-FH-FM failure envelopes of the FBJF have similar profiles and follow the same trend under different scour conditions.